ADAPTING TO LIFE CRISIS OF AGING: ROLE OF PERSONALITY STYLES AND COGNITIVE APPRAISAL IN ELDERLY WOMEN - Urquijo, Sebastián; Monchietti, Alicia; Krzemien, Deisy (Anales de Psicología / Annals of Psychology, 2008)
The debate about the factors that influence on coping to critical events persists. This paper proposes, first, to evaluate the coping strategies to critical life events of aging, that are used by old women, and second, to provide some insight into that debate, examining the role of both personality styles and cognitive appraisal on the prediction of the use of coping strategies in old age. It was applied a set of instruments to a sample of 212 participants: Brief-COPE, MIPS, Cognitive Appraisal Scale, a questionnaire about the socio-educative data and a focalized interview to examine the critical life events of aging. Results showed the most of coping styles and strategies was correlated with determined personality styles, as it was expected according to the Millon´s bipolar model of personality. It was evidenced the existence of significant differences in the coping and in the personality styles according to the mode of cognitive appraisal of the situation. Results contribute to emphasize the role of both the personality styles and the cognitive appraisal on coping strategies to the life crisis of aging in elderly women.